A Survey Paper on Data security in Cloud Computing - Sajjan, RS; Ghorpade, Vijay; Dalimbkar, Vishvajit (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is group of services for example software system storage, network and hardware these type of services are provided to user. Cloud storage is easily access anywhere anytime of the data because cloud is work in remote location. It uses the storage service provided by the cloud provider. Data is not secure in the cloud because the unauthorized user can try to use of the private data. So providing the data security it uses the different encryption method to protect the data. So that in the proposed study it use the multilevel encryption algorithm. In the multilevel encryption it combines two different algorithms for providing the better security.